Characterization of the inheritance of field-evolved resistance to diamides in the fall armyworm (Spodoptera frugiperda) (Lepidoptera: Noctuidae) population from Puerto Rico. - Omar Posos-Parra; David Mota-Sanchez; Barry R Pittendrigh; John C Wise; Christina D DiFonzo; Eric Patterson (PLoS ONE, 2024)
The fall armyworm (Spodoptera frugiperda) is one of the most destructive pests of corn. New infestations have been reported in the East Hemisphere, reaching India, China, Malaysia, and Australia, causing severe destruction to corn and other crops. In Puerto Rico, practical resistance to different mode of action compounds has been reported in cornfields. In this study, we characterized the inheritance of resistance to chlorantraniliprole and flubendiamide and identified the possible cross-resistance to cyantraniliprole and cyclaniliprole. The Puerto Rican (PR) strain showed high levels of resistance to flubendiamide (RR50 = 2,762-fold) and chlorantraniliprole (RR50 = 96-fold). The inheritance of resistance showed an autosomal inheritance for chlorantraniliprole and an X-linked inheritance for flubendiamide. The trend of the dominance of resistance demonstrated an incompletely recessive trait for H1 (♂ SUS × ♀ PR) × and an incompletely dominant trait for H2 (♀ SUS × ♂ PR) × for flubendiamide and chlorantraniliprole. The PR strain showed no significant presence of detoxification enzymes (using synergists: PBO, DEF, DEM, and VER) to chlorantraniliprole; however, for flubendiamide the SR = 2.7 (DEM), SR = 3.2 (DEF) and SR = 7.6 (VER) indicated the role of esterases, glutathione S- transferases and ABC transporters in the metabolism of flubendiamide. The PR strain showed high and low cross-resistance to cyantraniliprole (74-fold) and cyclaniliprole (11-fold), respectively. Incomplete recessiveness might lead to the survival of heterozygous individuals when the decay of diamide residue occurs in plant tissues. These results highlight the importance of adopting diverse pest management strategies, including insecticide rotating to manage FAW populations in Puerto Rico and other continents.